Bigger fish to fry : a theory of cooking as risk, with Greek examples - Sutton, David E. (David Evan) (New Anthropologies of Europe: Perspectives and Provocations, 2021)
"What defines cooking as cooking, and why does cooking matter to the understanding of society, cultural change and everyday life? This book explores these questions by proposing a new theory of the meaning of cooking as a willingness to put oneself and one's meals at risk on a daily basis. Richly illustrated with examples from the author's anthropology fieldwork in Greece, Bigger Fish to Fry proposes a new approach to the meaning of cooking and how the study of cooking can reshape our understanding of social processes more generally"--